Cadangan sekim perumahan di atas lot 1172,1173,1176,2994,2995,6839,6841 & 6843 mukim 11. Sungai Dua, Seberang Perai Utara / Mohammad Aizat Ja'afar ... [et al.] - Ja'afar, Mohammad Aizat; Mohammad Hanafi, Muhammad Aqil; M Jemeyy, Muhammad Syareenizam; Mohd Kadari, Muhammad Saiful Hidayat
Architectural drawing, structural key plans & rubrics, ESTEEM result, truss & rubrics, slab (continuous & simply supported) & rubrics, beam (continuous & simply supported) & rubrics, column & rubrics, foundation & rubrics, staircase & rubrics